1964
DOI: 10.1136/bmj.2.5411.720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propranolol (Inderal) in Angina Pectoris: Preliminary Report

Abstract: Cardiac Infarction-Sharland JRNAL MEDICAL JOUJRNAL that there has been a significant change in policy since 1936, when Levine recommended a period of six to eight weeks in bed, with an appropriate convalescent period. Alternatively, it is possible that there is an increasing occurrence or recognition of milder cases.While most would acknowledge the considerable psychological benefits which are seen in a patient who is able to resume work, there are very few data concerning the physical effects of resumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1966
1966
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 10 publications
(8 reference statements)
1
27
0
Order By: Relevance
“…Propranolol is now undergoing extensive clinical testing (70,77,117,118). There is some question, however, whether the demonstrable antiarrhythmic effect is due to fl blockade or to some other effect (69,93).…”
Section: It Also Acts As An Antifibrillatory Substance (20)mentioning
confidence: 99%
“…Propranolol is now undergoing extensive clinical testing (70,77,117,118). There is some question, however, whether the demonstrable antiarrhythmic effect is due to fl blockade or to some other effect (69,93).…”
Section: It Also Acts As An Antifibrillatory Substance (20)mentioning
confidence: 99%
“…A favourable response to propranolol in patients with angina pectoris can be shown after a short period of treatment. For example, Hamer, Grandjean, Melendez & Sowton (1964) showed that the exercise tolerance of patients with angina pectoris improved after a single dose of propranolol 5 mg i.v. This dose is less than that used in the present study and would be expected to have no effect on P50.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinically useful b-blocker was propranolol, introduced in the 1960s 36 and still used today. Other available agents include bisoprolol, atenolol, labetalol, carvedilol, metoprolol, and nebivolol.…”
Section: Beta-blockersmentioning
confidence: 99%